PENGARUH BOARD STRUCTURE DAN OWNERSHIP STRUCTURE TERHADAP VALUE RELEVANCE OF ACCOUNTING INFORMATION MELALUI INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI - Jevilia Widyatama; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the direct and significant influence between board structure and ownership structure to value relevance of accounting information. It is also to know the indirect influence of the board structure and ownership structure on value relevance of accounting information through intellectual capital disclosure as the mediating variable. The samples used in this research were 72 manufacturing companies listed on Indonesia Stock Exchange  from 2010-2015.  The data processed by using WarpPLS software version 5.0.The result of research found the positive affect of board structure on intellectual capital disclosure, negative affect of ownership structure on intellectual capital disclosure, positive influence of board structure toward value relevance of accounting information, positive influence of ownership structure to value relevance of accounting information, positive influence of intellectual capital disclosure to value relevance of accounting information. The intellectual capital disclosure successfully mediated the influence of the board structure on value relevance of accounting information, but the intellectual capital disclosure fails to mediate the influence of the ownership structure on the value relevance of accounting information.